Gender Differences in Students' Interpersonal Communication - Emma Dwi Ariyani; Dini Hadiani (CSRC Publishing, Center for Sustainability Research and Consultancy Pakistan, 2019)
Objective: Interpersonal communication is an essential element of communication that creates meaningful social relationships in the academic environment. Students who have good interpersonal communication skills will be capable of interacting with others. However, it was reported that some students still have a low capacity for interpersonal communication caused by various factors, and one of them is gender. This research attempts to investigate the students' interpersonal communication concerning gender and to find out whether there is a difference between male and female students in terms of interpersonal communication. Methodology: This study was conducted through a descriptive method. The subject of this study includes 88 students consisting of 66 male and 22 female students at one state polytechnic in Bandung, Indonesia. The data were collected in terms of interpersonal communication and gender. Results: The results show that male students had a slightly higher score of interpersonal communication than females. Regarding the significant elements of effective interpersonal communication, it was found that there are differences in the dominant component of interpersonal communication between male and female students. Female students dominated the area of equality, indicating that they have a more dominant ability to position themselves as equivalent to their communication partners to create comfortable communication. Male students dominated the area of openness, empathy, supportiveness, and a positive attitude showing that they have a more dominant ability to show a willingness to communicate honestly and full of understanding, so they were able to give support and positive thought. Implication: The study recommends the use of appropriate communication activities that can encourage the students to be open, to be supportive, and to be positive. This condition will enable teachers to choose and apply the appropriate methods in the teaching and learning process to support the development of students' interpersonal communication.